2014
DOI: 10.1371/journal.pone.0113300
|View full text |Cite
|
Sign up to set email alerts
|

The Potent Cdc7-Dbf4 (DDK) Kinase Inhibitor XL413 Has Limited Activity in Many Cancer Cell Lines and Discovery of Potential New DDK Inhibitor Scaffolds

Abstract: Cdc7-Dbf4 kinase or DDK (Dbf4-dependent kinase) is required to initiate DNA replication by phosphorylating and activating the replicative Mcm2-7 DNA helicase. DDK is overexpressed in many tumor cells and is an emerging chemotherapeutic target since DDK inhibition causes apoptosis of diverse cancer cell types but not of normal cells. PHA-767491 and XL413 are among a number of potent DDK inhibitors with low nanomolar IC50 values against the purified kinase. Although XL413 is highly selective for DDK, its activit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
39
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(42 citation statements)
references
References 61 publications
2
39
0
Order By: Relevance
“…We found that 5 µM of DDKi and a pre-treatment time of 4 hours were required to substantially block CHK1 activation by HU in HCC1954 cells (Supplementary Figure 1A). HCC1954 is a breast cancer cell line that expresses high levels of both DDK subunits and exhibits robust decrease in MCM2 phosphorylation in response to the prototype DDK inhibitor, PHA-767491 (DDKi) [18]. As shown previously, CHK1 activation was almost completely eliminated by pre-treatment with the DDK inhibitor PHA-767491 ( Figure 1A).…”
Section: Ddk Has a Primary Role In Initiating Replication Checkpoint supporting
confidence: 62%
See 2 more Smart Citations
“…We found that 5 µM of DDKi and a pre-treatment time of 4 hours were required to substantially block CHK1 activation by HU in HCC1954 cells (Supplementary Figure 1A). HCC1954 is a breast cancer cell line that expresses high levels of both DDK subunits and exhibits robust decrease in MCM2 phosphorylation in response to the prototype DDK inhibitor, PHA-767491 (DDKi) [18]. As shown previously, CHK1 activation was almost completely eliminated by pre-treatment with the DDK inhibitor PHA-767491 ( Figure 1A).…”
Section: Ddk Has a Primary Role In Initiating Replication Checkpoint supporting
confidence: 62%
“…The DDK inhibitors, PHA-767491 and XL413, were synthesized as described previously [18]. ATR inhibitor (VE-821, #A2521) and Camptothecin (#A2877) was from APExBIO.…”
Section: Cell Lines and Reagentsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, extended XL413 treatment in HeLa cells seems to merely delay progression through S phase rather than completely shut down replication. This perhaps provides a mechanistic explanation for why XL413 fails to induce apoptosis efficiently in cancer cells (Sasi et al., 2014). It is also important to note that several drug screens have been carried out using Mcm2 S40 phosphorylation as a marker of DDK activity.…”
Section: Discussionmentioning
confidence: 99%
“…Because it has been difficult to map mammalian origins of replication and there is no consensus binding site for known origins (Leonard and Mechali 2013), application of the Calling Card method to human DDK and to other proteins should identify functional origins that are used over many cell cycles. Furthermore, our studies are highly significant because inhibitors of DDK are in clinical trials against cancer and the Calling Card system could be used to help determine their effects on cells (Sasi, et al 2014, Swords, et al 2010). …”
Section: Conclusion and Future Usesmentioning
confidence: 99%